Intensitas Bermain Gadget dengan Suspek Gangguan Pemusatan Pikiran dan Hiperaktivitas (GPPH) pada Anak - PA, Pratiwi; Alvina, Alvina (Jurnal Biomedika dan Kesehatan, 2022)
BACKGROUND In these modern times, gadgets are not only owned by adults, but teenagers and children have also used them. Childhood is a golden period which is a period of conducive growth and development of children. Many parents have given and let their children play with gadgets. Gadgets can have negative effects that interfere with a child's development level. Attention Deficit Hyperactivity Disorder (ADHD) is a behavioural and neurocognitive disorder characterized by age-inappropriate developmental level, hyperactivity, inability to focus and impulsive behaviour. ADHD appears from childhood and can persist into adolescence and adulthood. Excessive gadget exposure is thought to be one of the triggers of ADHD. The purpose of the research is to determine the relationship between the intensity of playing gadgets with and suspected ADHD. METHODS The study was conducted on 92 kindergarten and elementary school students in West Jakarta in September-November 2019. The method was cross-sectional. The instruments used were a questionnaire about the identity and intensity of playing gadgets and a Skala Penilaian Perilaku Anak Hiperaktif Indonesia (SPPAHI) questionnaire for early detection of ADHD in children. Data analysis using the chi-square test with a significance level of p <0.05.RESULTSChi-square test showed no significant relationship between age with suspected ADHD p = 0.625, there was a significant relationship between sex with suspected ADHD (p = 0.000), and there was a significant relationship between the intensity of playing gadgets with a suspected ADHD (p = 0.000). CONCLUSION There is a significant relationship between gender and intensity of playing with gadgets with suspected ADHD in children. KEYWORDS: Gadget intensity, ADHD, Children.